Free Floating Ventricular Shunt Catheter Between Lateral Ventricles: A Case Report of an Unusual Ventriculoperitoneal Shunt Complication - Erol, Fatih Serhat; Cakin, Hakan; Ozturk, Sait; Donmez, Osman; Kaplan, Metin (Turkish Neurosurgical Soc, 2013)
Ventriculoperitoneal (VP) shunt proximal tip disconnection is rarely seen as a shunt complication. Shunt dysfunction and hydrocephaly can develop due to this disconnection. Presented here is a case of a disconnection of the ventricular catheter from the shunt valve, which passed between both lateral ventricles by free floating in the brain CT. The patient was operated on for hydrocephaly. The dysfunctional shunt valve and peritoneal catheter were removed and a new VP shunt system was implemented. Although some publications report that the ventricular catheter can be disconnected from the shunt valve, can adhere to the intraventricular structures, and can be a source of infection, no studies similar to the current case were found in the literature reporting a free floating ventricular catheter between the lateral ventricles.
Keywords: Hydrocephaly; Shunt dysfunction; Free ventricular catheter